2019
DOI: 10.3390/ijms21010001
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds with Antioxidant Properties from Canola Meal Extracts Inhibit Adipogenesis

Abstract: The extraction of phenolic compounds from canola meal produces functional health products and renders the canola meal a more digestible animal feed. The extracted phenolics may have novel bioactivity worth investigation. In this study, several solvents were evaluated for their ability to extract phenolic compounds from canola meal: water (WE) and various 80% organic solvent/water mixtures of methanol (ME), acetone (AE), ethanol (EE), butanol (BE), chloroform (CE) and hexane (HE). The in vitro antioxidant and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
1
23
0
2
Order By: Relevance
“…The antioxidant activities of sinapoyl malate and sinapoyl glucose were reported to be comparable to conventional antioxidants such as butylated hydroxyanisol (BHA), butylated hydroxytoluene (BHT), or trolox (Thiyam et al, 2006;Peyrot et al, 2020b). In addition, antioxidant activity of Canola meal extract was also studied by Hussain et al (Hussain et al, 2020). Their results showed that SinA and sinapine exhibited good radical scavenging activity towards 2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS).…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…The antioxidant activities of sinapoyl malate and sinapoyl glucose were reported to be comparable to conventional antioxidants such as butylated hydroxyanisol (BHA), butylated hydroxytoluene (BHT), or trolox (Thiyam et al, 2006;Peyrot et al, 2020b). In addition, antioxidant activity of Canola meal extract was also studied by Hussain et al (Hussain et al, 2020). Their results showed that SinA and sinapine exhibited good radical scavenging activity towards 2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS).…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…Additionally, anti-obesity properties of phenolic compounds of canola have been studied using adipogenic differentiation inhibition of a murine mesenchymal stem cell line (C3H10T1/2). Significant adipogenesis and pancreatic lipase inhibitory activities were found after treatment of 2-3 mg/mL canola meal extract through the downregulation of the peroxisome proliferatoractivated receptor gamma (PPARγ) signaling pathway [37].…”
Section: Obesitymentioning
confidence: 99%
“…The transformation of C3H10T1/2 cells into mature adipocytes requires adipogenic agents such as IBMX, DEX and insulin which have proven sufficient to induce differentiation within 12 days (Schwind et al, 2017). Troglitazone or rosiglitazone can also be used to cause differentiation (Hussain et al, 2020). In a culture containing DMEM media and heatinactivated FBS, L-glutamate and antibiotics, C3H10T1/2 cells are cultivated at 37°C in a humidified atmosphere of 5% CO2.…”
Section: C3h10t1/2 Cell Linementioning
confidence: 99%